Distinct immune responses confer partial resistance to Fusarium wilt in tomato landraces - Tzionis, Antonis; Artymatas, Giorgos; Kyratzis, Angelos C.; Dimitriadi, Stavroula; Tsolakidou, Maria Dimitra; Pantelides, Iakovos S. (My University, 2025)
Cypriot tomato landraces exhibit partial resistance to Fusarium wilt through distinct jasmonic and salicylic acid-mediated immune responses, offering promising genetic resources for breeding durable tomato cultivars. Fusarium wilt, caused by Fusarium oxysporum f. sp. lycopersici (Fol), is a major constraint on global tomato (Solanum lycopersicum) production, with few sustainable control measures available. This study assessed six Cypriot tomato landraces for resistance to Fol and explored the mechanisms underlying their defense. Pathogenicity assays under controlled growth conditions identified two landraces, ARI00732 and ARI00733, with partial resistance and improved growth performance compared to the susceptible cultivar Ailsa Craig. A second pathogenicity trial using sterilized and non-sterilized soils revealed no significant contribution of soil microbiota, suggesting intrinsic plant defenses as the primary mechanism. In vitro assays showed that root exudates from these landraces neither inhibited Fol growth nor altered fungal chemotropism. Gene expression analysis revealed distinct defense strategies: ARI00732 displayed strong induction of jasmonic acid (JA)-responsive genes (MYC2, LoxD, PDF1.2), whereas ARI00733 upregulated salicylic acid (SA)-associated Pti5 gene and the antioxidant defense gene APX1. These findings demonstrate that complementary JA- and SA-mediated pathways contribute to resistance. This work highlights the potential of tomato landraces as a source of durable resistance traits and provides a foundation for breeding programs targeting Fusarium wilt.
Keywords: Plant-pathogen interactions; Vascular wilt disease; Defense signaling pathways; Solanaceae germplasm